Electrical devices obtained from polymeric precursors process - Carvalho, Claudio Luiz [UNESP]; Peruzzi, Raphael Otavio [UNESP]; Solano, Rudi A. V. [UNESP] (Springer Nature, 2006)
Nowadays, many investments have been made in the area of superconductor materials, with the aim to improve their potential technological applications. Applications on the energy transport using cables, to get high resolution images in the medicine use high magnetic fields, high speed signals use superconductor devices all of them are in crescent evidence and they are showing that the future is coming and next for this new kind of materials. Obviously that everything of this is possible due to the increasing of research with new materials, where the synthesis, characterization and applications are of the mainly objective of these researches. The production of cable for the energy transport has been in advanced stage as the bulks production is too. However, the film production that to aim at the electronic devices area is not as developed or it still need expensive investments. Thinking about that, we are developing a research where we may increase the relation of cost/benefits. Thereby, we are applying the polymeric precursors method to obtain films that will be used in the built of electronic devices. Thin films (mono and multilayers, on crystalline or metallic substrates, controlled thickness) of the BSCCO system have been obtained from dip coating deposition process with excellent results in terms of preferential orientation, controlled thickness, a large area, which may indicate future applications. Based on these results, we present an electrical circuit and their principal characteristics as superconductor transition (85K), transport current density and structure. DC four probes method, scanning electron microscopy, digital optical microscopy and X-ray diffractometry were some techniques used for the characterization of this superconductor electric device. © 2006 Materials Research Society.
Keywords: Crystalline materials; Energy transfer; Magnetic fields; Scanning electron microscopy; Superconducting materials; X ray diffraction analysis; Dip coating deposition; Superconductor electric devices; Superconductor transition; Superconducting cables